# I need help asap please

3(k+3)+20≥2

Step 1. Firstly expand the bracket. leaving 3k + 9 + 20 >= 2Step 2. Simplifyleaving 3k + 29 >= 2Step 3. Subtract 29 from both sidesleaving 3k >= (2-29=-27)Step 4. Divide both sides by 3leaving k>= (-27/3 = -9)k >= -9
anotay1
22 August 2017
Thank you
kaydence
22 August 2017
3(k+3) ≥ -18k+3 ≥ -6k ≥ -9
Ryan T.
24 August 2017
3(k+3) more or equal to -183k+9 more or equal to -183k more or equal to -18-9=-27k more or equal to -27/3= -9****I couldn't do those symbols from the key board, that's why I wrote instead of putting the sign.Hope it will help you.
26 August 2017
3(k+3) +20 more or equal to 23k+9+20 more or equals to 23k+29More or equals to 23k more or equals to 2-29=-273k   >= -27k>= -27/3=-9k>=-9
26 August 2017
3(k+3)+20>=23k+9>=20-23k+9>=-183k>=-27k>=-9
mridulagarwal
03 September 2017
3(k + 3) + 20>_23k + 9 + 20>_23k + 29 >_23k + 29 - 29>_2 - 293k>_ -273k/3 >_-27/3k>_ -9
willowgreen4
07 September 2017
3(k+3)+20>=2Opening the bracket, we have3k+9+20 >= 23k+29 >= 2Taking 29 to the other side of the inequality, it becomes -29 on the other side3k >= 2-293K >= -27Divide through by 3 (the sign of the inequality wont change because 3 is a non negative number i.e 3>0)k >= -27/3k >= -9QED
sbrainy
08 September 2017
k<=3
raj.anuraag
16 September 2017
3(k+3)+20>=23k+9+20>=23k+29>=23k>=-27k>=-9
rishi1404
05 June 2018